PREVENTIVE MEASURES FOR IRON DEFICIENCY ANEMIA AMONG ADOLESCENTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article is aimed at analyzing the causes of the spread of iron deficiency anemia among adolescents, reviewing international experiences in preventing this condition, and proposing effective preventive measures that can be applied in the context of Uzbekistan. The article is intended to provide practical recommendations not only for healthcare professionals but also for teachers, parents, and representatives of government agencies.